(untitled) (Research, Society and Development, 2021)
Hyaluronic acid is a substance that is becoming increasingly popular in minimally invasive aesthetic procedures on the face. Although the human body itself has endogenous hyaluronic acid, it becomes scarce over the years with the natural aging of the skin, resulting in loss of volume and decay throughout the face. Given this, hyaluronic acid dermal fillers appeared, which have the capacity of volumizing soft tissues and promoting harmony and aesthetics to the face. Therefore, this study aimed to investigate the knowledge of the use of hyaluronic acid in facial filling interventions taking into consideration its properties, the level of effectiveness and possible complications. This study consisted of a basic, qualitative, descriptive integrative review based on the PubMed and Virtual Health Library search platforms, exploring the terms hyaluronic acid, hyaluronan, dermal fillers, and aesthetics. Articles were included in the time range from 2016 to 2021 in the English language and the search yielded 16 articles. The selected articles showed that the use of hyaluronic acid brings great levels of effectiveness and satisfaction to patients, but evidenced the need for retreatment sessions months later for maintenance, it is safe, because the most common complications cease mostly within two weeks and without the need for intervention, besides being a substance with excellent properties and rheological characteristics. It can be concluded that the use of hyaluronic acid is effective, safe and has ideal properties in dermal facial filling.